Black and green pigments based on chromium-cobalt spinels - Eliziario, Sayonara A. [UNESP]; de Andrade, Jeferson M.; Lima, Severino J. G.; Paskocimas, Carlos A.; Soledade, Luiz E. B.; Hammer, Peter [UNESP]; Longo, Elson [UNESP]; Souza, Antonio G.; Santos, Leda M. G. (Elsevier B.V. Sa, 2011)
Chromium and cobalt oxides are widely used in the manufacture of industrial pigments. In this work, the Co(Co(2-x)Cr(x))O(4) powders with different chromium concentrations (x = 0, 0.25 and 1) were synthesized by the polymeric precursor method, heat treatment between 600 and 1000 degrees C. These powders were characterized by X-ray diffraction, infrared spectroscopy, colorimetry, UV-vis absorption and X-ray photoelectron spectroscopies. Even with the addition of chromium, the XRD patterns revealed that all powders crystallize in a single spinel cubic structure. The spinets with higher cobalt amount, Co(CoCr)O(4) and Co(Co(1.75)Cr(0.25))O(4), displayed a dark color, without the Co(3+) reduction observed in Co(3)O(4) between 900 and 950 degrees C. The spinel with higher chromium amount, CoCr(2)O(4), was green. The colors were directly related to the occupation of tetrahedral and octahedral sites by the chromophores, as well as to the different oxidation states of chromium and cobalt. The different optical band gap values estimated from UV-vis spectra suggested the existence of intermediary energy levels within the band gap. X-ray photoelectron spectroscopy confirmed an increasing presence of Co(III) and a decreasing amount of Cr(VI) with cobalt enrichment. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Optical materials; Oxides; X-ray photo-emission spectroscopy